On-line Support to People with Autism, their Families and Therapists in the State of Emergency - Glumbić, Nenad; Đorđević, Mirjana (Specijalna edukacija i rehabilitacija, 2020)
Following the declaration of an international state of emergency due to the COVID-19 pandemic outbreak, in many countries, direct treatment of people with autism was suspended. With the introduction of the state of emergency in Serbia, effective from mid-March 2020, all forms of direct support to people with autism and their families were prevented. Instead, new forms of support in the virtual environment were increased and introduced. The purpose of this paper is to present forms of online support for people with autism during the state of emergency, in which the authors participated. Beneficiary users were either direct (people with autism spectrum disorder) or indirect (their parents and therapists). Depending on the time of effectuation, support was synchronous (in real-time) or asynchronous (appropriate materials available on the internet without direct contact between the support provider and client). Synchronous form of direct beneficiary users was the Youth Club, which included six people with high-functioning autism whose social skills treatment was accomplished in small groups, once a week, via video chat. Indirect beneficiary users in real-time support were parents who used online counseling services and early intervention providers who attended one-time online mentoring support. Asynchronous models included specially designed guidance for caregivers of people with autism in a state of emergency and a social story. Past experience indicates the need to create special protocols for dealing with people with autism in the state of emergency.